Piperacillin population pharmacokinetics in critically ill patients with multiple organ dysfunction syndrome receiving continuous venovenous haemodiafiltration: effect of type of dialysis membrane on dosing requirements. (10th February 2016) - Ulldemolins, Marta; Martín-Loeches, Ignacio; Llauradó-Serra, Mireia; Fernández, Javier; Vaquer, Sergi; Rodríguez, Alejandro; Pontes, Caridad; Calvo, Gonzalo; Torres, Antoni; Soy, Dolors
Abstract: Objectives: This multicentre study aimed to describe the pharmacokinetics (PK) of piperacillin in critically ill patients with multiple organ dysfunction syndrome (MODS) receiving continuous venovenous haemodiafiltration (CVVHDF), to identify the sources of PK variability and evaluate different dosing regimens to develop recommendations based on clinical parameters. Patients and methods: Nineteen patients with MODS and CVVHDF receiving piperacillin/tazobactam were enrolled from three tertiary hospitals (95 plasma samples). Population PK modelling and Monte Carlo simulations were performed using NONMEM v7.3 ® . Results: Patients' median age was 70 years (range 39–82), median weight was 80 kg (45–129), median APACHE II score at admission was 21 (13–33) and median SOFA score on the day of study was 11 (8–21). The final population PK model was characterized by CL (L/h) = 6.11 * [weight (kg)/80] 1.39  * CLMEMB . If membrane = 1.5 m 2 AN69ST, CLMEMB  = 1; if membrane = 0.9 m 2 AN69, CLMEMB  = 0.51. Monte Carlo simulations showed that: (i) to maintain unbound piperacillin concentrations above the MIC for the bacteria for 100% of dosing interval T (100% f u T >MIC ), patients receiving CVVHDF with 1.5 m 2 AN69ST membranes required doses of 4000 mg q8h for the treatment of bacteria with a susceptibility to piperacillin close to the clinical breakpoint (MIC = 8–16 mg/L) (2000 mg q8h was sufficient for patients with CVVHDF using 0.9 m 2 AN69 membranes); and (ii) for the treatment of bacteria with high susceptibility to piperacillin (MIC <4 mg/L) or for the attainment of a more traditional pharmacodynamic target (50% f u T >MIC ), 2000 mg q8h sufficed regardless of type of membrane and body weight. Conclusions: Our results suggest that type of membrane and body weight should be considered for piperacillin dose titration in critically ill patients with MODS and CVVHDF requirement.